2007
DOI: 10.1002/ejoc.200700032
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Synthesis of Drugs and Bioactive Natural Products

Abstract: Catalytic reactions are a key element in the design of sustainable chemical processes. As witnessed in the field of transition metal-catalysed processes, only those reactions that are reliable over a broad substrate range and tolerant toward a multitude of functional groups have found their way into the repertoire of preparative chemists. Natural product

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
68
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(72 citation statements)
references
References 189 publications
0
68
0
4
Order By: Relevance
“…More recently it was confirmed that relatively simple organic molecules could be highly effective and remarkably enantioselective catalysts of a variety of fundamentally important transformations (de Figueiredo and Christmann, 2007;Enders et al, 2007;Pellissier, 2007). Several examples on application of organocatalysis in combination with homogeneous catalysis for enantioselective reactions are summarized in Enders et al (2007).…”
Section: Organo-chemical Transformationsmentioning
confidence: 97%
“…More recently it was confirmed that relatively simple organic molecules could be highly effective and remarkably enantioselective catalysts of a variety of fundamentally important transformations (de Figueiredo and Christmann, 2007;Enders et al, 2007;Pellissier, 2007). Several examples on application of organocatalysis in combination with homogeneous catalysis for enantioselective reactions are summarized in Enders et al (2007).…”
Section: Organo-chemical Transformationsmentioning
confidence: 97%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Since the pioneering work in this area by the groups of MacMillan, [13] and Barbas, [14] numerous publications have appeared in which the design, synthesis and uses of a variety of organocatalysts is described. Today, one of the biggest challenges in the synthesis of organic compounds is the implementation of procedures that are more friendly to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…[22,23] The Michael addition is considered as one of the most powerful tools for the formation of C-C bonds. [1][2][3][4][5][6][7][8][9][10][11][12] In recent years, the number of publications on the study of this organocatalytic reaction has increased considerably. [1] In 1980, Seebach and coworkers reported the reaction of achiral enamines with β-nitrostyrene with good yields and excellent diastereoselectivities.…”
Section: Introductionmentioning
confidence: 99%
“…The employment of a metal-free approach [10] stems from our recent findings on the intramolecular base-catalyzed synthesis of 1, from readily available precursors 3 (Scheme 2).…”
mentioning
confidence: 99%